Comparison of individual and collaborative game-based learning using tablet in improving students’ knowledge in primary classroom environment - Jamil Azhar, Sheikh Ahmad Firdaus; Ab Jalil, Habibah; Ma'rof, Aini Marina; Mohd Nazan, Ahmad Iqmer Nashriq; Erzam Marlisah; Nasharuddin, Nurul Amelina; Ismail, Suriani; Ismail, Ismi Arif (UiTM Press, 2022)
In the 21st century, mobile games have become a growing interest among children, including primary school students. This can be a great opportunity for instructors to utilize mobile games approaches and students' interest in games for education teaching and learning purposes, specifically in the primary classroom environment. However, there is no study yet considering the effect between individual and collaborative game-based learning (GBL) on students' knowledge. Experimental research was conducted in a public primary school to address the issue. The present study successfully determined the effectiveness of individual and collaborative GBL using tablets in improving students' knowledge in a primary classroom environment. Three groups of Standard Five students were given a pre-test before the intervention, followed by each group were taught using different approaches of conventional learning, individual and collaborative GBL, respectively. Subsequently, the students were given a post-test after the intervention. The test of homogeneity results indicated that the model was normally distributed and could be used for the intervention. The results of analysis of covariance (ANCOVA) on students' post-test scores show the collaborative GBL had the highest mean, which was 9.324 at Day 4. Additionally, the collaborative group also had the highest mean of trials and success rate during intervention among the three groups as the days increased, which were 3.8 and 0.6, respectively. The collaborative GBL was the most effective among three different approaches. The students had a group discussion to share and organize ideas and critical thinking between their group members on what they have learned from previous intervention days into the current intervention session. The major findings of the present study revealed the potential of collaborative GBL using the tablet in the primary classroom environment in improving students' understanding, knowledge, problem-solving, communications and critical thinking skills.